Liturgiese koorsang as wyse van kerklike verkondiging: "n Prinsipiële besinning vanuit hermeneutieshomiletiese perspektief - Kloppers, E. C. (Hervormde teologiese studies, 1994)
Liturgical choral song as a form of ecclesiastical proclamation: A fundamental reflection from a hermeneutical-homiletical perspective Certain reformed churches have, traditionally, disapproved of choral singing. This has been due either to one-sided or inconsistent theological arguments, or to overreaction to bad choral singing. This article strives to show that, in principle, there is no difference between the kerugma of preaching and that of a choral work, and that liturgical choral singing can be regarded as a form of church proclamatioru Proclamation is examined from a hermeneutical-homiletical point of view, in order to show that there are no fundamental differences between the ‘hearing’ of a choral work and listening to an ‘ordinary’ spoken sermon.